Performance of CrCN-WS2 hard/soft composite coated tools in dry cutting of titanium alloys. (June 2020) - Lian, Yunsong; Long, Yangyang; Zhao, Guolong; Mu, Chenliang; Li, Xuemu; Deng, Jianxin; Xie, Chaoping
Graphical abstract: Fig. 3. The cross-section micro-morphology of the CrCN-WS2 hard/soft composite coating. Highlights: CrCN-WS2 hard/soft composite coated dry cutting tool was prepared. Performance of composite coated tool in dry cutting titanium alloys was studied. CWT was more suitable for processing titanium alloys at a higher speed ( v ≥ 60 m/min). The anti-adhesion performance of CWT was the best of the four cutting tools. Abstract: In this work, a CrCN-WS2 hard/soft composite coating was deposited on the surface of cemented carbide cutting tools to improve the cutting performance of the tool during dry cutting titanium alloys. To analyse the improvement, the cutting performance of CrCN-WS2 hard/soft composite coated tool (CWT) was compared to that of traditional uncoated tool (NT), CrCN hard-coated tool (CT) and WS2 soft-coated tool (WT) at different cutting speeds. The results show that among the four cutting tools, CWT exhibited the best cutting performance. Compared to those of NT, the main cutting force F z of CWT decreased by 21.8 %–45.4 %, the radial thrust force F y decreased by 8.2 %–34.0 %, the adhesion height of CWT decreased by 31.0 % and the cutting temperature of CWT decreased by 6.7 %–34.8 %. It was also shown that CWT is more suitable for high-speed cutting of TC4 titanium alloy.